Implementation Measurement Heavy Utilize Macrobending on Fiber optics Using Microcontroller Media - Taj putra Akbar as ad; Mochammad Junus; Yoyok Heru Prasetyo Isnomo (Jurnal Jaringan Telekomunikasi, 2022)
Fiber optics is a light-utilizing signal transmission medium and can be used in a wide variety of sensing sensors. Optical fiber has multifunctional sensing capabilities, namely strain, pressure, temperature, and acoustic signals with a high level of sensitivity. In this study, optical fiber will be used as a mass sensor by utilizing the macro bending method with microcontroller media. The data analysis carried out was compares the graph when the fiber optic is given a certain load, by the number certain windings and when bending with a certain diameter will then be made formula for measuring mass with optical fiber. Load or load mass = 0 gr, 200 gr, 400 gr, up to 10 kg with 9 turns and ¼ inch, ½ inch, 5/8 inch, ¾ inch, and 1 inch diameter hose. In this study, the results of weight measurement using an equation obtained from measuring the power loss against the load used are formed in a graph which results in the linier equation that is entered converted into a formula for finding the load which is then inputted into the android code so that it can be processed properly.